Subcloning and Transformation of a Portion of the Gene Encoding the ISG-75 N-terminal Domain of Trypanosoma brucei - Cornell, Robert F.; Nolan, Derek P.; Voorheis, Paul (Trinity Student Medical Journal, 2004)
Objectives: African trypanosomiasis is a parasitic disease caused by Trypanosoma brucei and transmitted by the tsetse fly. Trypanosomes evade the immune system by altering their surface structure, which contains a layer of 107 variant surface glycoprotein (VSG) that partially shield a number of underlying invariant surface glycoproteins (ISGs).1,2 Understanding invariant surface glycoproteins has been the recent focus of study for vaccine development and chemotherapy. Since its discovery, ISG-75 has received little study despite the fact its sequence is unique and not related to any other ISG. The focus of this project was to subclone the portion of the gene encoding the 440 amino acid N-terminal domain of ISG-75. The recombinant domain was purified and used to raise antibodies for use as a reagent to determine the orientation of ISG-75 in live bloodborne trypanosomes. The orientation of this protein is important, both for academic reasons in the attempt to understand its function and practically, as a possible target for parasite control by chemotherapy or immune control via a single chain. This involves the production of a single domain recombinant antibody that would be small enough to pass the VSG barrier and reach its ISG target. Understanding which part of the protein is exposed externally on the cellular surface is critical in selecting the portion of the protein to target. Methods: Polymerase Chain Reaction (PCR) was performed using genomic DNA to obtain the N-terminal domain of ISG-75. The gene fragment encoding the N-terminal domain of ISG-75 and the pET-21a vector were successfully double digested with the restriction enzymes, Nde1 and Not1. The insert and vector were cut from 1% agarose gels and extracted from the gel material. They were then ligated together and transformed into E. coli. Results: The N-terminal domain measured 1354 basepairs after PCR. After incubating the insert and vector with the restriction enzymes the N-terminal domain was visible in the appropriate region. Two smaller band fragments 600 and 754 basepairs in length were also identified. The pET-21a vector was found in the appropriate region and measured 5443 basepairs in length. E. coli colony counts where performed on both the ligation mixture and control LB agar plates. Thirteen colonies were found on the ligation mixture plate.